2017
DOI: 10.5001/omj.2017.08
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of Malaysian Aloe vera Leaf Extract on Selected Fungal Species of Pathogenic Otomycosis Species in In Vitro Culture Medium

Abstract: The antifungal effect of alcohol extracts of Malaysian leaf is better than the aqueous extract for ( < 0.001). Malaysian has a significant antifungal effect towards

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 3 publications
1
20
0
1
Order By: Relevance
“…Another study by Mbajiuka et al (2014) revealed that ethanol extracts of A. vera had water MIC compared to aqueous and methanol extracts against E. coli, S. aureus and C. albicans. More or less similar findings were obtained by Kahing (2011) were found to support the findings of Saniasiaya et al (2017). So from all these experimental findings it may be said that besides of allopathic treatment naturally sourced compounds may be used to formulate new and more potent antifungal agents against otomycosis.…”
Section: Clinicomycological Studiessupporting
confidence: 80%
“…Another study by Mbajiuka et al (2014) revealed that ethanol extracts of A. vera had water MIC compared to aqueous and methanol extracts against E. coli, S. aureus and C. albicans. More or less similar findings were obtained by Kahing (2011) were found to support the findings of Saniasiaya et al (2017). So from all these experimental findings it may be said that besides of allopathic treatment naturally sourced compounds may be used to formulate new and more potent antifungal agents against otomycosis.…”
Section: Clinicomycological Studiessupporting
confidence: 80%
“…Another study affirmed that alcoholic A. vera leaf extracts can be used as a therapeutic agent to inhibit the growth of some selected fungal species that causes infection of the middle and external auditory canal of the ear such as Aspergillus sp. and Candida albicans (Saniasiaya et al, 2017).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…vera species have different applications. In this regard, they are utilized for their antiulcer (Suvitayavat, Sumrongkit, Thirawarapan, & Bunyapraphatsara, ), antihyperlipidemic (Pothuraju, Sharma, Onteru, Singh, & Hussain, ), antifungal (Saniasiaya, Salim, Mohamad, & Harun, Jan), antiviral (Alves, Perez‐Fons, Estepa, & Micol, ), antimicrobial (Ferro et al, ), anticancer (El‐Shemy et al, ), antioxidant (Boudreau & Beland, ), burn wound healing (Choi & Chung, ), antidiabetic (Pothuraju, Sharma, Onteru, et al, ), immunomodulator (Pugh, Ross, ElSohly, & Pasco, ), antihypertensive (Saleem et al, ), antiobesity (Misawa et al, ), and hepatoprotective effects (Chandan et al, ). Moreover, A .…”
Section: Introductionmentioning
confidence: 99%